The Impact of Domain Knowledge on Structured Data Collection and Templated Note Design - Windle, T.; McClay, JC.; Windle, JR. (Applied Clinical Informatics, 2013)
Objective: The objective of this case report is to evaluate the importance of specialized domain knowledge when designing and using structured templated notes in a clinical environment.Methods: To analyze the impact of specialization on structured note generation we compared notes generated for three scenarios: 1) We compared the templated history of present illness (HPI) for patients presenting with a dermatology concern to the dermatologist versus the emergency department. 2) We compared the evaluation of chest pain by ED physicians versus cardiologists. 3) Finally, we compared the data elements asked for in the evaluation of the gastrointestinal system between cardiologists and the liver transplant service (LTS). We used the SNOMED CT representation via BioPortal to evaluate specificity and grouping between data elements and specialized physician groups.Results: We found few similarities in structured data elements designed by and for the specific physician groups. The distinctness represented both differences in granularity as well as fundamental differences in data elements requested. When compared to ED physicians, dermatologists had different and more granular elements while cardiologists requested much more granular data. Comparing cardiologists and LTS, there were differences in the data elements requested.Conclusion: This case study supports the importance of domain knowledge in EHR design and implementation. That different specialities should want and use different information is well supported by cognitive science literature. Despite this, it is rare for domain knowledge to be considered in EHR implementation. Physicians with correct domain knowledge should be involved in the design process of templated notes.
Keywords: Information seeking behavior; medical informatics; knowledge management; systems analysis; knowledge; notes; workflows and human interactions